2020
DOI: 10.1029/2020ja028570
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal and Interhemispheric Ionospheric Response to 2009 and 2013 SSW Events in the African‐European and Indian‐East Asian Sectors

Abstract: The ionospheric response to two sudden stratospheric warming (SSW) events that occurred during low (2009) and moderate solar activity (2013) around 10°E (±10°) African-European and 95°E (±10°) Indian-East Asian sectors is investigated. The total electron content (TEC) obtained from a meridional chain of stations in the two sectors are used to understand the interlongitudinal and interhemispheric response to these SSW events. Significant depletion of daytime TEC was observed after the onset of 2009 SSW around t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 69 publications
1
9
0
Order By: Relevance
“…As evident from Figure, the SSW occurred on day number 56 (January 24). Even though the SSW of January 2008 is minor warming (since there is no reversal of zonal wind), it is one of the strongest recorded events in terms of the enhancement in Polar Stratospheric Temperature (PST) (27,28) . As is obvious in Figure 2, the zonal mean zonal wind at 10 hPa do not show any reversal associated with SSW, albeit there is a small decrease at around day number 50.…”
Section: The Role Of Tides In Modulating the Ssw Induced Effectsmentioning
confidence: 99%
“…As evident from Figure, the SSW occurred on day number 56 (January 24). Even though the SSW of January 2008 is minor warming (since there is no reversal of zonal wind), it is one of the strongest recorded events in terms of the enhancement in Polar Stratospheric Temperature (PST) (27,28) . As is obvious in Figure 2, the zonal mean zonal wind at 10 hPa do not show any reversal associated with SSW, albeit there is a small decrease at around day number 50.…”
Section: The Role Of Tides In Modulating the Ssw Induced Effectsmentioning
confidence: 99%
“…Recently, Kakoti et al. (2020) showed semidiurnal modulation to be a primary feature of SSW time TEC variations by studying interhemispheric and interlongitudinal asymmetry in ionospheric responses to SSW events of 2009 and 2013 at African‐European and Indian‐East Asian sectors. Zhang et al.…”
Section: Introductionmentioning
confidence: 99%
“…Mostly, the observations from various reports discussed above unambiguously confirmed that the stratospheric effect of warming perturbed the upper atmosphere, particularly the ionosphere. Though a number of studies are available that provide a comprehensive account of ionospheric response to SSW, the inferences drawn on the subject are largely based on the very well researched and reported major SSW event of 2009, followed by SSW event of 2013 (e.g., Kakoti et al., 2020; Zhang et al., 2020), or by considering a few other SSW events. With low solar activity and unusual progression, solar cycle 24 lasted from December 2008 to December 2019 and is considered to be the weakest cycle in the last 100 years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They attributed this poleward movement to the increased amplitude of the upward E × B drift caused by the SSW event. Similarly, Kakoti et al (2020) linked the enhancement in TEC magnitude during the mid-January 2013 SSW event to the semidiurnal signature associated with the SSW event. During the mid-January 2013 SSW event over the Asian sector along 150°E longitude, Goncharenko et al (2013) reported significant ionospheric perturbations at the northern EIA compared to the southern crest They attributed these perturbations to the influence of the lower atmosphere.…”
mentioning
confidence: 99%